2013
DOI: 10.1371/journal.pone.0062784
|View full text |Cite
|
Sign up to set email alerts
|

MAR Elements and Transposons for Improved Transgene Integration and Expression

Abstract: Reliable and long-term expression of transgenes remain significant challenges for gene therapy and biotechnology applications, especially when antibiotic selection procedures are not applicable. In this context, transposons represent attractive gene transfer vectors because of their ability to promote efficient genomic integration in a variety of mammalian cell types. However, expression from genome-integrating vectors may be inhibited by variable gene transcription and/or silencing events. In this study, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
(43 reference statements)
0
19
0
Order By: Relevance
“…Matrix attachment regions can increase expression levels of the transgene in stably transfected CHO cells . However, the characteristics and mechanism of MARs function have not been elucidated, and further studies are needed to develop improved methods for transgene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrix attachment regions can increase expression levels of the transgene in stably transfected CHO cells . However, the characteristics and mechanism of MARs function have not been elucidated, and further studies are needed to develop improved methods for transgene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Scaffold/matrix attachment regions (S/MARs) can block transgene silencing and increase transgene expression levels and stability in host cells . In addition, S/MARs can also reduce variations in transgene expression among different cells to some extent, and the rate of transgene genomic integration can be increased . However, some reports have shown that S/MARs have inconsistent effects on transgene expression .…”
mentioning
confidence: 99%
“…In experiments where Foxa1 was overexpressed, the CMV/EF1alpha promoter was replaced by a minimal cytomegalovirus (CMV) promoter for both Foxa1 and GFP expressions. The piggyBac transposase expression vector (pCS2+U5V5PBU3) was previously described (Ley et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The piggyBac transposase expression vector (pCS2+U5V5PBU3) was previously described (Ley et al, 2013).…”
Section: Plasmidsmentioning
confidence: 99%
“…Furthermore, both SB and PB have been used to construct cell lines for inducible transgene expression under the control of the Tet-On system [37,38 ,40]. Although PB-derived cell lines often have fairly constant levels of protein production over time in the absence of selection, the addition of a MAR element to the donor vector reduced the effects of gene silencing [41,42]. Besides the transposon systems mentioned here, others have recently been introduced under the trade name Leap-In TM (DNA2.0, Menlo Park, CA).…”
Section: Non-targeted Transgene Integrationmentioning
confidence: 99%